Effects of some cations on the formation of 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) in a model system. (15th June 2016) - Yu, Di; Yu, Shu-Juan
Highlights: Fe 2+ and Fe 3+ inhibited the formation of PhIP in a model system of phenylacetaldehyde and creatinine. Ca 2+ and Mg 2+ enhanced the formation of PhIP in a model system of phenylacetaldehyde and creatinine is first proposed. A possible mechanism for the action of the cations during PhIP formation in the model system is proposed. Abstract: The present study aimed to investigate in detail the changes to 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) and its precursors in the presence of some cations (i.e., K +, Na +, Ca 2+, Mg 2+, Fe 2+ and Fe 3+ ) in a creatinine/phenylacetaldehyde model system. Results showed that PhIP yields decreased when Fe 2+ and Fe 3+ were added to a mixture of phenylacetaldehyde and creatinine. This decrease may be attributed to the fact that Fe 3+ can form complexes with various properties with creatinine and accelerate creatinine degradation. This pathway can disturb the reaction with phenylacetaldehyde, influence aldol condensation product formation, and suppress PhIP formation. Furthermore, Ca 2+ and Mg 2+ enhanced PhIP content. Such enhancement may be attributed to the fact that CaCl2 and MgCl2 promote aldol and aldol condensation product reactions with ammonia and formaldehyde. A possible mechanism for the action of cations during PhIP formation in a model system is also proposed.